Codex Amiatinus of the Latin Vulgate Bible and Its Birthplace - White, H. J. (Gorgias Press, 2006)
White takes the reader through a historical puzzle revolving around the date of the Vulgate manuscript Codex Amiatinus. He demonstrates that the manuscript falls in the eighth century and traces its origins to Italy
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: RELIGION / Biblical Criticism & Interpretation / General